A two-stage energy tuning strategy via salt and glycine programmed DNA-engineered crystals. Issue 99 (30th November 2021) - Du, Yanqiu; Zhou, Xiang; Jin, Jing; Liang, Haojun; Men, Yongfeng; Jiang, Wei
Abstract : This work presents a two-stage energy tuning strategy by salt and glycine for preparing high-quality DNA-engineered crystals at room temperature. Abstract : To obtain high-quality DNA-engineered crystals at room temperature, a two-stage energy tuning strategy by first adding NaCl and then glycine (Gly) is proposed. The addition of Gly can exquisitely balance the attraction and repulsion energies for crystallization. The state transition induced by energy rather than temperature is significant for a biosystem.